1995
DOI: 10.1677/jme.0.0140263
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of glucose transport by parathyroid hormone and insulin in UMR 106–01, a clonal rat osteogenic sarcoma cell line

Abstract: This study characterizes the actions of insulin and parathyroid hormone (PTH) on the glucose transport system in the rat osteogenic sarcoma cell line UMR 106-01, which expresses a number of features of the osteoblast phenotype. Using [1,2-3H]2-deoxyglucose (2-DOG) as a label, UMR 106-01 cells were shown to possess a glucose transport system which was enhanced by insulin. In contrast, PTH influenced glucose transport in a biphasic manner with a stimulatory effect at 1 h and a more potent inhibitory effect at 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 24 publications
0
25
0
1
Order By: Relevance
“…Our analysis with osteoblastic cells suggests a dominant role of high affinity glucose transporters but cannot give an accurate figure since it is likely that several GLUTs account for overall glucose uptake by the cells. Thomas and co-workers [28] found a stimulatory effect of PTH on 2DG uptake in UMR cells at 1 h (and ] thymidine incorporation into DNA (lower panels) in PyMS cells exposed to PTH (left panels) or to IGF I and insulin (right panels). Cells were grown for 3 days in FCS-containing medium, rinsed with serum-free medium, and exposed for 24 h to serum-free medium.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our analysis with osteoblastic cells suggests a dominant role of high affinity glucose transporters but cannot give an accurate figure since it is likely that several GLUTs account for overall glucose uptake by the cells. Thomas and co-workers [28] found a stimulatory effect of PTH on 2DG uptake in UMR cells at 1 h (and ] thymidine incorporation into DNA (lower panels) in PyMS cells exposed to PTH (left panels) or to IGF I and insulin (right panels). Cells were grown for 3 days in FCS-containing medium, rinsed with serum-free medium, and exposed for 24 h to serum-free medium.…”
Section: Discussionmentioning
confidence: 97%
“…PTH was found to increase lactate production and to decrease citrate decarboxylation by bone and osteoblastic cells [19,[24][25][26][27]. Moreover, it stimulated 2DG transport in UMR 106-01 rat osteogenic sarcoma cells after 1 h, and inhibited 2DG transport after 16 h [28]. PTH increased [ 14 C] glucose incorporation into glycogen in cultured rat calvaria cells but not in fibroblasts [6].…”
Section: Introductionmentioning
confidence: 99%
“…Results from in vitro studies, utilising osteoblast cultures, and in vivo studies have indicated that insulin increases bone anabolic markers, modulating collagen synthesis (Rosen & Luben 1983), alkaline phosphatase production (Canalis 1983, Kream et al 1985, Yamaguchi et al 1993, parathyroid hormone (PTH) responsiveness (Thomas et al 1995) and glucose uptake (Ituarte et al 1989). Importantly, the heterogeneous distribution of IR in neonatal rat calvaria was reported subsequently (Thomas et al 1996).…”
Section: Insulin and The Insulin Receptormentioning
confidence: 99%
“…This concept stems from early studies that illustrated cultured osteoblasts metabolize glucose to lactate (12)(13)(14) and that osteoanabolic hormones and growth factors stimulate glucose consumption (15,16). Recent studies have confirmed these findings using more refined genetic and molecular techniques and elaborated on mechanisms of glucose acquisition and utilization (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%